Intonasi Pembacaan Al-Qur’an: Kritik terhadap Konsep Khafdu Al-Shaut dalam Al Tibyan Fi Adabi Hamalati Al-Qur’an - Itmam Aulia Rakhman (Journal on Education, 2024)
This article discusses the intonation of reciting the Quran and critiques the concept of khafdu al-shaut in the book Al Tibyan fi Adabi Hamalati Al-Qur'an. The concept of khafdu al-shaut, which refers to lowering the intonation of reciting the Quran in certain verses that tend to discredit God in the context of Quranic etiquette. The article highlights the differences of opinion between Ibrahim al-Nakha'i and scholars of Quranic studies regarding the etiquette of reciting the Quran. Furthermore, it emphasizes the importance of understanding the general etiquette of reciting the Quran, which emphasizes raising the recitation of the Quran as a form of reverence towards God. By referring to various sources and scholars' perspectives, this article provides profound insights into the practice of reciting the Quran and the importance of understanding the proper etiquette in reciting the holy book for the Muslim community.